A study of the essential oil of Pinus insularis Endl. (Pinaceae) - Aranez, Jose T.
The needles of Pinus insularis Endl. yields 0.4% of a colorless oil which turns yellowish upon exposure to air and light. It has a specific gravity of 0.8629 and a refractive index of 1.4695. Using column and thin layer chromatography, it was found to contain five main constituents.